E- Learning Berbasis Web dengan Penerapan Model Problem Based Learning pada Mata Pelajaran Rekayasa Perangkat Lunak - Saputra, Rusli; Putri, Yessy Prima; Adhavini, Chasvi; Defiariany, D (SAFE-Network, 2023)
The world of education is a dimension that cannot be separated from the influence of technology. One form of technology development used in the world of education today is an electronic learning application known as e-learning. The application of learning is an important point in the application of a learning model and the learning model is one of the determinants of the success or failure of teaching and learning activities to achieve the learning objectives that have been formulated. The learning objectives are not only how students can understand the given theory but also the development of aspects such as cooperation, respect for opinions and problem solving abilities. To fulfill this development, the learning strategy should accommodate students for the development of learning in the world of education. One of the learning models that can be developed and adopted to place students at the center of learning is the application of the Problem Based Learning (PBL) model which is combined in the form of web-based e-learning. The purpose of this study is to design a web-based e-learning learning information system with the application of the PBL model. The software development method in designing this learning information system uses the SDLC (System Development Life Cycle) method using the PHP and MySQL programming languages. The research will be conducted by observing activities and obstacles in the teaching and learning process of Software Engineering subjects at SMK Maritim Nusantara Padang Pariaman. This research produces a Web-based e-learning learning information system with the application of the Problem Based Learning model. With the application of the learning model students can understand the theory and have the ability to solve problems related to these subjects. The system is supported by e-learning applications, so that it can help students learn anytime and anywhere.